2006
DOI: 10.1515/epoly.2006.6.1.793
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of poly(vinyl alcohol) by addition of methacryloyl groups: characterization by FTIR and NMR and optimization of reaction conditions by RSM

Abstract: Abstract:The modification of poly(vinyl alcohol) (PVA) with glycidyl methacrylate (GMA) in DMSO catalyzed by TEMED is reported in this paper. PVA was dissolved in DMSO and reacted with GMA at 30 ºC in a closed vessel under N 2 gas bubbling for 24 hours. The reaction was characterized by FTIR and NMR ( 1 H, 13C/DEPT and HETCOR) spectroscopies. The reaction occurs by transesterification through the insertion of methacryloyl groups into PVA chains and probably with the formation of glycidol as a by-product. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The FTIR spectrum of PVA-GMA100 hydrogel (Figure 1a) presents a broad band at 3421 cm -1 assigned to the -OH stretching, a band at 2936 cm -1 assigned to C-H vibrational stretching, and a band at 1094 cm -1 assigned to C-O vibrational stretching. Moreover, the bands at 1727 and 1642 cm -1 , which are assigned to C=O and C=C stretching, proceeding from methacrylate groups of GMA used for modifying PVA [36]. The FTIR spectrum of CS (Figure 1d) shows a broad band between 3100-3600 cm -1 assigned to -OH and to N-H vibrational stretching in which the -OH stretching overlaps the N-H one.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…The FTIR spectrum of PVA-GMA100 hydrogel (Figure 1a) presents a broad band at 3421 cm -1 assigned to the -OH stretching, a band at 2936 cm -1 assigned to C-H vibrational stretching, and a band at 1094 cm -1 assigned to C-O vibrational stretching. Moreover, the bands at 1727 and 1642 cm -1 , which are assigned to C=O and C=C stretching, proceeding from methacrylate groups of GMA used for modifying PVA [36]. The FTIR spectrum of CS (Figure 1d) shows a broad band between 3100-3600 cm -1 assigned to -OH and to N-H vibrational stretching in which the -OH stretching overlaps the N-H one.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…In only a few studies, synthesis of block copolymers of vinyl acetate and NVP has been reported with the cobalt‐mediated living polymerization and reversible addition‐fragmentation chain transfer polymerization techniques . For this purpose, to provide grafting of NVP to the PVA chains by means of free‐radical polymerization, first, a PVA–GMA prepolymer was prepared by the chemical modification of PVA with GMA monomer according to a method published in the literature . It has been reported that a transesterification reaction between a GMA monomer and PVA takes place in the media of polar‐aprotic solvents such as DMSO and DMF, and the vinyl methacrylate side of the GMA is attached to PVA chains from hydroxyl groups of PVA .…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, to provide grafting of NVP to the PVA chains by means of free‐radical polymerization, first, a PVA–GMA prepolymer was prepared by the chemical modification of PVA with GMA monomer according to a method published in the literature . It has been reported that a transesterification reaction between a GMA monomer and PVA takes place in the media of polar‐aprotic solvents such as DMSO and DMF, and the vinyl methacrylate side of the GMA is attached to PVA chains from hydroxyl groups of PVA . The glycidol side of GMA has occurred as a byproduct during the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations